The Problem of Rationality in Sociology - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2013)
Rationality seems to be the meeting point of sociology and philosophy. “Rationality” is a controversial concept. Historically, the problems of rationality, normativity, social action, and meaning-adequacy in sociology have its closest relationships with epistemology. The aim of this essay is to articulate and explicate the parallel “problems of rationality” in sociology and philosophy. This is done in two parts. The first looks at sociologists’ attempts to articulate conceptually the relation between rationality and normativity. The problem of the relationship of rationality and normativity in sociology appears early in a classical and modern sociology but appears consequently in many more hidden ways in connection with epistemological naturalism. The article argues that the radical critique of epistemology and philosophy in contemporary neopraxiological empiricism is misdirected due to a misconception about the relationship between rationality and a priori.